Evaluating an inclusive blended learning environment in EFL: a flipped approach. Issue 5 (4th July 2022) - Andujar, Alberto; Nadif, Fátima Zahra
Abstract: This research explores the use of an inclusive blended learning environment in an EFL class. A total of 39 students, including 6 participants who suffered from physical and cognitive disabilities followed a flipped learning model over a period of two months. In order to create this inclusive blended learning model, a series of videos were developed to deliver three B1 didactic units of an English coursebook and were designed to take into consideration students' physical and cognitive disabilities. Captions, text and sign language were provided together with the videos, following a "universal design" in which a wide range of students are considered when elaborating the materials. These videos were viewed by participants before their lessons in order for the teacher to devote in-class time to those learners who may have struggled to understand and put into practice the contents and explanations in the videos. In-depth interviews, a perception scale of the flipped learning experience and an evaluation of the tools implemented were used with a special focus on those students with disabilities. Several implications and pedagogical recommendations were drawn.